2015
DOI: 10.1007/s10551-015-2648-7
|View full text |Cite
|
Sign up to set email alerts
|

Exporting an Inherently Harmful Product: The Marketing of Virginia Slims Cigarettes in the United States, Japan, and Korea

Abstract: Ethical issues surrounding the marketing and trade of controversial products such as tobacco require a better understanding. Virginia Slims, an exclusively women’s cigarette brand first launched in 1968 in the USA, was introduced during the mid 1980s to major Asian markets, such as Japan and Korea, dominated by male smokers. By reviewing internal corporate documents, made public from litigation, we examine the marketing strategies used by Philip Morris as they entered new markets such as Japan and Korea and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 42 publications
0
15
1
Order By: Relevance
“…Slim cigarettes were designed and marketed as women-specific tobacco products when first developed almost a half century ago [3] [4]. However, this study found no significant correlations between the market share of slim cigarettes and the smoking prevalence rates, especially the smoking prevalence rates among females [5].…”
Section: Introductioncontrasting
confidence: 56%
“…Slim cigarettes were designed and marketed as women-specific tobacco products when first developed almost a half century ago [3] [4]. However, this study found no significant correlations between the market share of slim cigarettes and the smoking prevalence rates, especially the smoking prevalence rates among females [5].…”
Section: Introductioncontrasting
confidence: 56%
“…In Korea, Ovale e-cigarettes are categorised as tobacco products, given that the product contains nicotine. Hence, these marketing activities appear to contravene Korea's Tobacco Business Act and National Health Promotion Act, which prohibits cigarette company marketing activities that are targeted at youth or women 11 12. Ovale's tactics, targeting youth, engaging in CSR, product placement, sponsorship, and web-based interactive communications, resemble the strategies of conventional tobacco companies 13–22…”
mentioning
confidence: 99%
“…We also included all lipstick shaped packs in our initial sample of feminine packs. We did not include all slim shaped packs in the initial dataset because, unlike Int J Public Health | Owned by SSPH+ | Published by Frontiers lipstick shaped packs which are almost exclusively associated with women, slim packs could have a broader appeal across gender [36,47].…”
Section: Feminine Appeals Codingmentioning
confidence: 99%